(3TQM eYdbI GeQF GdbjSs - (3GeQD GdbjS Hf MLQ Hf GdMGQK GdcfOj, ef Hfj Bcd GdeQGQ , J (B80 (3b g`s
(3ChdgG (B:s
(3Ef gPG ef eMGSf GdCjGe GdUGdMg Jbhd hbO eGd GdZjW HfG eYkG YbQJ HYjQi jG CeQF GdbjS eGfRd s
(3BNQgG (B:s
(3dCfgG THg JdWNgG HGdWjf hGdeGA GdcOQ HCUhd GdHUd GdHQi dCfgG eJdWNg HGdWjf hGdJQGH JeJ bUjOI GeQF GdbjS s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHYs
(3GdTGYQ gh GeQh GdbjS Hf MLQ Hf GdMGQK GdcfOi GdeJhai (B80 (3b g`s
(3GdfSNI HgG MhGTs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B351s
Keywords: (3GdCOHs